Comparative Analysis on Sharia Governance in Islamic Non-Profit Organizations across Indonesia, Malaysia and Brunei Darussalam - Laily Dwi Arsyianti; Irfan Syauqi Beik; Nur Laili Ab Ghani; Muhamad Abduh; Adora Aurahma; Arifia Marsila Hayati (AL-MUZARA'AH, 2025)
This study examines the governance practices of Islamic non-profit organizations in Indonesia, Malaysia, and Brunei Darussalam. The thorough examination is conducted through a framework developed based on the standards set by the Islamic Financial Services Board (IFSB), Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), as well as the core principles of zakat and waqf. A qualitative approach was carried out using content analysis methods from literature reviews, and then NVivo was used to collect, classify, map reports and analyse further about the topics. This study found that sharia NPO governance practices in Indonesia, Malaysia and Brunei Darussalam still need to be explained in detail, as well as several indicators. This study addresses previously unexplored issues, particularly regarding sharia-compliant Non-Profit Organizations (NPOs). In this regard, it pioneers research that examines and compares the governance frameworks of NPOs in Indonesia, Malaysia and Brunei Darussalam. The scope of this research focuses on regional areas with a global Muslim majority, namely Indonesia, Malaysia and Brunei Darussalam. Practitioners in the field of sharia-compliant NPOs can utilise this research as a reference and policy foundation. This action can help in advancing social initiatives cross-country level and can be a reference for establishing governance framework standards in sharia-based NPOs with practitioners and experts in the field.